VARIABILITY ANALYSIS OF VOLUME TRANSPOR IN SUNDA STRAIT : Abstract - Ishak Jumarang NIM. 224 02 005, Muhammad
Abstract: Research have been to analysis of variability volume transpor in Sunda strait with use numerical model Barotropik 3D simulation of POM (The Princeton Ocean Model) modified by Ningsih (2000). This simulation to find out variability of volume transport resulted ENSO, Monsoon and Dipole Mode interaction. The are two simulation scenario have to do i.e. the 1st scenario just use the wind field to generated and the 2nd scenario use two generated i.e. wind field and elevation difference of the Java Sea Indian Ocean. The 1stscenario have to do during 9 year (1972-1974, 1981-1983, 1996-1998) and the 2nd scenario just have to do on El Nino event 1997-1998. The analysis of simulation results use cross correlation method between volume transport with sea surface temperature anomaly at Niño3.4, wind meridian velocity and Dipole Mode Index. The analysis has to do for El Niño, La Niña, normal and Dipole mode event. The analysis results show that Monsoon and ENSO have positive correlation with volume transport (r > 0.5), while the Dipole Mode have negative correlation (r < -0.7). When La Niña event 1998 that coincide DM(-), along this year, the volume transport toward Java Sea with maximum intensity in May (1,54 Sv) and minimum in October (0,14 Sv). When the normal event, the volume transport in Sunda strait toward Indian Ocean when west monsoon (January) until first east monsoon (June) and the other way when east monsoon (July) until first west monsoon (December). When El Niño event 1972-1973, 1982-1983, and 1997-1998, they have difference volume transport pattern. The model simulation of the 2nd scenario show that along year the volume transport toward Indian Ocean (-0.18 to 0.72 Sv) except on February to April 1998 (0.12 Sv to 0.009 Sv). The cross correlation coefficient between volume transport with sea surface temperature anomaly at Niño3.4, Dipole Mode Index and monsoon with this scenario in succession result r(5)=0.53; r(4)=0.51 and r(0)=0.70. The volume transport on 1st scenario have the similar pattern with Idris (2002) result i.e. 0.09 to 1.62 Sv while on the 2nd scenario have the similar pattern with Putri (2005)(-0.48 to 0.72 Sv); Wannasingha, etc, (2004) (-0.2 to 0.3 Sv); and Schiller, etc, (2005) (-0.5 + 0.45 Sv). The simulation results show that the 2nd scenario had results better than 1st scenario. The coefficient of cross correlation of each scenario show that the change of volume transport in Sunda Strait was influenced more dominant by monsoon than ENSO and Dipole Mode event.